Technology Entrepreneurship (ENT600) : Philips / Nur Faatihah Ahmad Redzuan - Ahmad Redzuan, Nur Faatihah (2021)
Philips is a well-known company that manufacturer of electronic products in Amsterdam, Netherlands. This company has been chosen to complete in case study under the subject of Technology Entrepreneurship (ENT600). The case study is to figure out about the background of company, organizational structure, products and services of Philips. One of the product have been selected from the company which is blender. Through this, we study about the blender technology which is basically a same technology used by hand blender, juice blender, food processor or chopper. Thus, the business, marketing and operating strategies used by the companies has been figure out to see how the company manage the product into the target market. Next, there are some problems that I analyze about this company by using SWOT analysis. All the information about the product has been studied. Due to the needs and demands by the existing users of the product, there have several problem that face by the company. They have an issues with the size of jar, the material it used, the shape of the container, style of cap or blade and speed settings. For example, they providing the smaller size which only enough for 1 litre. While the material it use for the jar is made by the plastic material which not really well in resistant the hard or hot foods and easily get scratch. After finding the problems of the product, I find out the solution based on the weaknesses that can be implemented by the company. This can help the company to find ways on how to overcome and meet customers' needs by making it more innovation. For example, provide enough space of jar and use a material that can resistant to any ingredient, modify the shape of container, provide removable cap in the centre and have more option in speed settings. With all the solution that have been suggested, the company can solve the problems in order to establish the new product to target market in the future. Lastly, some recommendations can be made in order to improve the products and services. They can improve the material of the jar by using glass material to make it more resistant toward variety of food. Not only that, offer more option of speed which have three range of speed from low to high that can be used with all type of food. All the recommendation very helpful to Philips and may act as a catalyst to strength up their company. As a result, Philips' Company can produce a lot of electronic that more advance with technology. Not only that, it can give a benefit to the consumers as well as help the company to increase the profits.